Relationship between knowledge level and readiness to face menarche with anxiety in grade v and vi students at sd inpres tello baru 1/1 - Juwita, Juwita (CV. Paperhome Indonesia, 2025)
Menarche is the first menstrual period marked by the emergence of physiological changes that include physical and mental changes. Indonesia has experienced a decline in menarche rates based on the results of the 2014 Riskesdas, there were 5.2% of children in Indonesia entering menarche under the age of 12 years. The arrival of menarche actually makes some young women afraid or anxious and consider menstrual blood to be a disease. Lack of knowledge and unpreparedness to face menarche can be the cause of this. Objective: To determine the relationship between the level of knowledge and readiness to face menarche with anxiety in female students in grades V and VI at SD Inpres Tello Baru 1/1. Method: This study uses quantitative descriptive with a cross-sectional analytical study approach. The population in this study was 70 respondents. The sampling technique used was total sampling, with a sample size of 70 respondents. Results: The results of the study showed that the level of knowledge about menstruation in grades V and VI at SD Inpres Tello Baru 1/1 was included in the good category, which was 72.9%, and readiness to face menarche was 87.1%, and anxiety was found in female students of 62.9%. The results of the Chi Square test showed that there was a significant relationship between the level of knowledge and readiness to face menarche with anxiety in female students (p = 0.000, p = 0.000). Conclusion: there is a significant relationship between the level of knowledge and readiness to face menarche with anxiety in female students in grades V and VI at SD Inpres Tello Baru 1/1